Clinical characteristics and outcomes of type 2 diabetes patients infected with COVID-19: A retrospective study (2020)
Diabetes and its related metabolic disorders have been reported as the leading comorbidities in patients with coronavirus disease 2019 (COVID-19). This clinical study aims to investigate the clinical features, radiographic and laboratory tests, complications, treatments, and clinical outcomes in COVID-19 patients with or without diabetes. This retrospective study included 208 hospitalized patients ( 45 years old) with laboratory-confirmed COVID-19 during the period between 12 January and 25 March 2020. Information from the medical record, including clinical features, radiographic and laboratory tests, complications, treatments, and clinical outcomes, were extracted for the analysis. 96 (46.2%) patients had comorbidity with type 2 diabetes. In COVID-19 patients with type 2 diabetes, the coexistence of hypertension (58.3% vs. 31.2%), coronary heart disease (17.1% vs. 8.0%), and chronic kidney diseases (6.2% vs. 0%) was significantly higher than in COVID-19 patients without type 2 diabetes. The frequency and degree of abnormalities in computed tomography (CT) chest scans in COVID-19 patients with type 2 diabetes were markedly increased, including ground-glass opacity (85.6% vs. 64.9%, P < 0.001) and bilateral patchy shadowing (76.7% vs. 37.8%, P < 0.001). In addition, the levels of blood glucose (7.23 mmolL 1 (interquartile range (IQR): 5.80–9.29) vs. 5.46 mmolL 1 (IQR: 5.00–6.46)), blood low-density lipoprotein cholesterol (LDL-C) (2.21 mmolL 1 (IQR: 1.67–2.76) vs. 1.75 mmolL 1 (IQR: 1.27–2.01)), and systolic pressure (130 mmHg (IQR: 120–142) vs. 122 mmHg (IQR: 110–137), P = 0.001) in COVID-19 patients with diabetes were significantly higher than in patients without diabetes (P < 0.001). The coexistence of type 2 diabetes and other metabolic disorders is common in patients with COVID-19, which may potentiate the morbidity and aggravate COVID-19 progression. Optimal management of the metabolic hemostasis of glucose and lipids is the key to ensuring better clinical outcomes. Increased clinical vigilance is warranted for COVID-19 patients with diabetes and other metabolic diseases that are fundamental and chronic conditions.